Formale Überqualifikation unter ost- und westdeutschen Beschäftigten - Christina Boll; Julian S. Leppin (Wirtschaftsdienst, 2014)
In der Debatte um Übergänge vom Bildungssektor in den Arbeitsmarkt werden Fragen nach einem guten Job-Matching aufgeworfen. Gleichzeitig wird ein Mangel an Fachkräften und Ineffizienzen am Arbeitsmarkt beklagt. Wie Überqualifikation am Arbeitsmarkt gemessen werden kann und welche Schlüsse sich aus den Ergebnissen ziehen lassen, zeigen die Autoren in diesem Beitrag. – – In the context of ongoing demographic and economic change, the full exploitation of resources in terms of the productive use of acquired qualifications is a vital challenge. Overeducation is adverse to this aim. It occurs if individuals attained a higher level of education than is required in their current jobs. Relying on SOEP data, Boll and Leppin investigate the prevalence of overeducation in East and West Germany from 1992 to 2011. Their results indicate that the magnitude of overeducation heavily depends on the measurement method employed as well as on region, gender and education. Earnings analyses reveal that people who are overeducated according to either their self-assessment or to the realized matches criteria are most severely harmed. The authors suggest that selection plays a reasonable role and conclude that labour market imperfections and shortcomings of the educational system have to be addressed by policy makers.
Keywords: E24; J24; J31; 330; Unterbeschäftigung; Messung; Arbeitsmarktintegration; Matching; Neue Bundesländer; Alte Bundesländer